PERBEDAAN HASIL PENUNDAAN SAMPEL FFP (Fresh Frozen Plasma) 36 JAM DAN 48 JAM TERHADAP PEMERIKSAAN APTT (Activated Partial Thromboplastin Time) - Novi Ersanto; Jhoni Pramanda Tubulau; Titik Sundari; Siti Nur Husnul Yusmiati (Jurnal SainHealth, 2024)
Blood transfusion is the transfer of blood from one person (donor) into the vein of another person (recipient). Blood components include cellular and non-cellular components. The results of the study were conducted to determine the differences in the results of 36-hour and 48-hour FFP (Fresh Frozen Plasma) samples stored at room temperature against APTT (Activated Partial Thromboplastin Time) examination. The sample was FPP (Fress Frozen Plasma) from Dr. Sotomo Hospital Surabaya, which obtained significant results, namely there was a difference in the plasma APTT value with a delay of 36 hours, plasma with a delay of 48 hours with plasma with a delay of 30 minutes or without delay, while the plasma APTT value with a 30-minute delay as a control for the normal APTT value. The Mann-Whitney statistical test showed that there was a significant difference (p<0.05) between 30-minute plasma with 36-hour delay plasma p=0.00 and 48-hour delay plasma with p=0.000. The conclusion in the hematological examination, especially the APTT examination, if there is a delay in the examination, it should be examined no more than two hours. Keywords: Fress Frozen Plasma, Activated Partial Thromboplastin Time